2011
DOI: 10.1016/j.rehab.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic education in persons with spinal cord injury: A review of the literature

Abstract: The global level of evidence on the effects of therapeutic education in persons with spinal cord injury is low because of the number of studies and their low statistical power and requires additional studies. However, the analysis of the literature allows for discussing the organization of therapeutic education in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…6 The cause of PrUs is multi-factorial, including biological, behavioral, and social components. Studies of medical therapies 9 and non-modifiable risk factors 10 far exceed those of behavioral treatments and modifiable risk factors. With the exception of daily skin checks and smoking, 11,12 evidence linking behavior to PrU outcomes is limited.…”
Section: Introductionmentioning
confidence: 99%
“…6 The cause of PrUs is multi-factorial, including biological, behavioral, and social components. Studies of medical therapies 9 and non-modifiable risk factors 10 far exceed those of behavioral treatments and modifiable risk factors. With the exception of daily skin checks and smoking, 11,12 evidence linking behavior to PrU outcomes is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have mainly focused on educational interventions [3436]. In addition to identifying self-management studies that include a focus on skin care and aim to prevent pressure ulcers in people with a SCI, the proposed systematic review aims to describe these interventions with regard to the active ingredients they include and their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the focus has primarily been on interventions of an educational nature (i.e. provision of information) [3436] (e.g. SCI University Online, Spinal Cord Essentials) [37, 38], recent years have seen a growing number of self-management interventions addressing skin care using other strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that even though statistical significance could not be reached, there was an obvious trend toward better overall survival in DLBCL-associated spinal cord compression patients who completely abrogated their neurological deficit. From this result, we suggested that decreases in comorbidities associated with spinal cord compression, such as cardiopulmonary dysfunction [18], poor infection control [19], and psychological problems [20], could play an important role in the superior overall survival observed in patients with DLBCL-associated spinal cord compression who received surgical decompression.…”
Section: Discussionmentioning
confidence: 99%